Pengaruh Waktu Reaksi Dan Penambahan Volume Enzim terhadap Pemurnian Selulosa-α Pelepah Sawit Menggunakan Enzim Xilanase Dari Trichoderma sp - Putri M F; Padil Padil; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Palm midrib is one of the solid waste from oil palm plantattions and there is approximately 35% α- cellulosa component. Cellulose which contained in waste palm midrib are very potential to transform into nitrocellulose raw material. Purify of cellulose above 92% can be used to make main propelan raw material or explosive matter. The purpose of this research was to got the best condition of addition from xylanase enzyme and the best time of reaction from purifying α-cellulose palm midrib process as a main nitrocellulose raw material. Palm midrib has to accomplished by several steps of purify such as extraction, hydrolysis, and delignyfication, and then continue to purifying process with xylanase enzyme on 60oc phase, pH 5, ratio of palm midrib: aquadest 1:25 in term of enzyme volume addition and time of reaction variation. The analyst of cellulosa that pass the hidrolysis show the purity α-cellulose is 86,48%. The best condition is able at enzyme volume addition 3 ml and time of reaction 90 menit with the purity of α-celluloseobtained 96,6%. So it can be concluded that α-cellulose of the palm midrib pass purity process used the xylanase enzyme can be used for the manufacture of nitrocellulose.Keyword :α-cellulosa,nitrocellulose, palmmidrib,purification,xylanase enzyme